1991
DOI: 10.1016/0736-5748(91)90036-l
|View full text |Cite
|
Sign up to set email alerts
|

Different in vitro response to rIL‐1β of newborn and adult rat astroglia

Abstract: In recent literature, lymphokines have been reported to be able to promote both proliferation and maturation of some glial populations. In this paper, we compare the effect of rIL-1 on newborn and adult rat astroglial cells in vitro. In newborn, but not in adult astrocytes, 100 U/ml of rIL-1 beta increase [3H]thymidine incorporation with a maximal response by 3 days as compared to the control untreated culture. In contrast, rIL-1 beta induces an increase of GFAP immunoreactivity both in newborn and in adult as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In this respect, it has been reported that the stimulatory effect of histamine and substance P on interleukin‐1 and interleukin‐6 production by rat astrocytes is mediated through an increase in [Ca 2+ ] i (Martin et al., 1992 ; Cadman et al, 1994). It has also been shown that TTN and Ro 5‐4864 stimulate the production of interleukin‐1 (Taupin et al, 1991, 1993), which is known to trigger astrocyte proliferation (Giulian and Lachman, 1985 ; Colasanti et al, 1991). Collectively, these observations indicate that the [Ca 2+ ] i increase induced by TTN either may directly stimulate DNA synthesis or may act indirectly through activation of cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been reported that the stimulatory effect of histamine and substance P on interleukin‐1 and interleukin‐6 production by rat astrocytes is mediated through an increase in [Ca 2+ ] i (Martin et al., 1992 ; Cadman et al, 1994). It has also been shown that TTN and Ro 5‐4864 stimulate the production of interleukin‐1 (Taupin et al, 1991, 1993), which is known to trigger astrocyte proliferation (Giulian and Lachman, 1985 ; Colasanti et al, 1991). Collectively, these observations indicate that the [Ca 2+ ] i increase induced by TTN either may directly stimulate DNA synthesis or may act indirectly through activation of cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…One surprising aspect of these results was the consistent antiproliferative effect of IL-1 for human fetal astrocytes, regardless of their basal proliferative activity . In neonatal rat astrocytes, Giulian and Lachman (1985) and others (Colasanti et al, 1991) have re- ported a mitogenic effect of IL-1 for astrocytes both in vitro and in vivo, but similar results were not detected in astrocytes cultured from adult bovine brain (Selmaj et al ., 1990) . In the human fetal cultures reported here tumor necrosis factor-a, a cytokine that is produced in IL-lß-stimulated human fetal astrocytes, also showed a slight antiproliferative effect on these cells, whereas interferon-y showed a mild mitogenic effect .…”
Section: Discussionmentioning
confidence: 80%
“…There was an increase in expression of the anti-inflammatory cytokine IL-10 and the pro-inflammatory cytokine IL-6, although there was less IL-6 under the hypoxia condition than there was when HUCB cells were added to the astrocyte culture during normoxia. IL-6, produced by neurons, astrocytes and microglia [39], promotes astrocyte proliferation [40] and gliosis [41] and can be neuroprotective in culture [42,43]. However, over-expression of IL-6 is associated with neurodegeneration, breakdown of the blood brain barrier (BBB), angiogenesis, increased expression of complement proteins, and impaired learning [44,45] while IL-6 knockout mice have less brain damage in response to focal cryo injury to the fronto-parietal cortex compared to control animals [46].…”
Section: Discussionmentioning
confidence: 99%